100 Must-Read Classic Novels. - Rennison, Nick (Bloomsbury Publishing PLC, 2009)
Want to become a classic novel buff, or expand your reading of some ofthe finest novels ever published? With 100 of the best titles fullyreviewed and a further 500 recommended, you'll quickly set out on ajourney of discovery.